Reconstructing the past and the poet: Grundtvig and the Anglo-Saxon Phoenix - Jørgensen, Lea Grosen (Grundtvig-studier, 2018)
In 1840, Grundtvig produced a Danish translation of the Anglo-Saxon poem The Phoenix that reflects some of his ideas concerning history, language, and Anglo-Saxon poetry.